Ultraviolet curing polyethylene cable material with high insulating property and preparation process thereof
By using ultraviolet light curing technology to blend low-density polyethylene with high-density polyethylene and phytic acid-nano TiO2 modified lignin and modified inorganic particle composite materials, the aging problem of insulated cable materials under temperature gradient was solved, and cable materials with high insulation performance and long service life were prepared.
Patent Information
- Application Number
- CN202510980117.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-16
- Publication Date
- 2025-10-28
AI Technical Summary
Existing insulated cable materials are prone to aging under temperature gradients, leading to structural changes and performance degradation, making it difficult to maintain stability in high-temperature environments.
A high-insulation polyethylene cable material was prepared by blending low-density polyethylene and high-density polyethylene, combining phytic acid-nano TiO2 modified lignin and modified inorganic particle composite materials, and using ultraviolet curing technology. The flame-retardant properties of phytic acid, the improved crystallinity of nano TiO2, and the insulation properties of modified inorganic particles were utilized to form a high-density cross-linked network.
It improves the mechanical properties, insulation properties, and flame retardant properties of cable materials, extends service life, slows down the aging process, and reduces production costs.
Smart Images

Figure BDA0005502685380000131
Abstract
Description
Technical Field
[0001] This invention relates to the field of cable material technology, and in particular to a high-insulation-performance ultraviolet-cured polyethylene cable material and its preparation process. Background Art
[0002] Insulated cable materials widely use petrochemical-based polymers such as polyethylene, polyvinyl chloride, and cross-linked polyolefins as the main matrix, and are modified with flame retardants, reinforcing fillers, and processing aids to meet the cable's requirements in terms of electrical performance, mechanical strength, thermal stability, and environmental resistance. To improve flame retardancy, aluminum hydroxide, antimony trioxide, or halogen-based flame retardants are usually added, while inorganic nanofillers are used to improve mechanical properties and thermal conductivity. In terms of processing technology, melt blending, radiation cross-linking, and thermosetting molding are commonly used to prepare the insulation layer or sheath structure.
[0003] Patent application CN108623877 discloses an insulating material for high-voltage DC cables and its preparation method. Compared with traditional cross-linked polyethylene insulation, this insulating material incorporates a cross-linking agent, reducing the cross-linking agent content while maintaining the same degree of cross-linking, extending the plasticizing time, and improving the insulation performance of the cable. However, the temperature gradient generated during cable operation can cause changes in the internal structure of the insulating material, accelerating its aging. Summary of the Invention
[0004] This invention aims to solve the above-mentioned technical problems and provides a high-insulation-performance UV-curable polyethylene cable material and its preparation process. The following technical solution is adopted:
[0005] One objective of this invention is to provide a high-insulation-performance UV-curable polyethylene cable material, comprising the following raw materials in parts by weight: 50-80 parts of first low-density polyethylene, 2-10 parts of second low-density polyethylene, 10-20 parts of high-density polyethylene, 5-15 parts of phytic acid-nano-TiO2 modified lignin, 1-4 parts of modified inorganic particle composite material, 1-4 parts of polyolefin elastomer, 0.5-1.5 parts of crosslinking agent, 0.5-1.5 parts of initiator, and 0.2-0.8 parts of antioxidant; wherein the phytic acid-nano-TiO2 modified lignin is obtained by the condensation reaction of alkali lignin and phytic acid while simultaneously doping with nano-TiO2; wherein the inorganic particles in the modified inorganic particle composite material include magnesium hydroxide and / or aluminum hydroxide, as well as fumed silica and nano-boron nitride, and the modifier is a composition of azobenzene and alkenylsilane coupling agent.
[0006] Low-density polyethylene (LDPE) has relatively low mechanical strength, but excellent flexibility, extensibility, and high transparency. The molecular chains of LPE contain numerous short branches and a small number of long branches. During the cross-linking and curing reaction, the short branches offer less resistance to the transformation from the molten state to the crystalline state, resulting in a highly regular crystalline structure. Destruction at high temperatures requires significant energy, thus allowing it to withstand high temperatures. Furthermore, the short branches in the amorphous phase can entangle with each other, acting as connecting molecular chains to form a cross-linked network with higher cross-linking density. This enhances the ability to deform uniformly under external forces, resulting in a more stable and less easily deformed structure. High-density polyethylene (HDPE) exhibits higher hardness, tensile strength, and creep resistance, demonstrating better mechanical properties. It maintains stability at high temperatures and retains a certain degree of toughness at low temperatures. Blending LPE and HDPE combines their advantages, significantly improving the structural performance of polyethylene cable materials. Polyolefin elastomers can improve the flexibility of cross-linked polyethylene and enhance its resistance to mechanical damage.
[0007] Phytic acid, also known as inositol hexaphosphate, contains a large amount of phosphorus (P) and -OH groups in its structure, making it an effective phosphorus-based flame retardant. During heating, it decomposes to release phosphate molecules, accelerating the carbonization of the matrix and isolating or slowing down heat transfer and mass exchange between polyethylene and the external environment, thus providing some protection. Lignin, containing numerous benzene rings, carbonyl groups, and phenolic hydroxyl groups, possesses strong carbon-forming ability and certain flame-retardant properties. Lignin also exhibits excellent antioxidant and UV-resistant properties, scavenging free radicals generated by light exposure and improving the aging resistance of polyethylene cable materials. Alkali lignin, with its alkaline groups, enhances the reactivity and compatibility of lignin in polyethylene, reducing its aggregation. Nano-TiO2 increases the crystallinity and cross-linking density of polyethylene, making it difficult for moisture to diffuse within the polyethylene insulation material, thereby inhibiting water treeing and extending service life. It also improves the thermal stability and glass transition temperature of polyethylene, allowing the polyethylene material to maintain stable performance over a wider temperature range. Phytic acid-nano TiO2 modified lignin introduces a large amount of phosphorus (P) into lignin through a condensation reaction with phytic acid, significantly improving its flame retardant properties. Furthermore, the presence of phytic acid allows lignin particles to be better dispersed in polyethylene. Lignin can significantly reduce the hygroscopicity caused by the addition of phytic acid, and works synergistically with nano TiO2 to improve the waterproofness of polyethylene cable materials.
[0008] In modified inorganic particle composite materials, magnesium hydroxide and aluminum hydroxide possess excellent insulation properties, improving the insulation resistance and dielectric strength of cable materials without compromising other properties. They also provide smoke suppression and flame retardancy, enhancing cable safety. Fumed silica promotes heterogeneous nucleation, resulting in smaller and more uniformly distributed grains in low-density polyethylene. It also forms strong interfacial interactions with the polyethylene matrix, enhancing the density of the polyethylene material and reducing the erosion of its internal structure by external environmental factors such as moisture and ultraviolet radiation. This allows cable sheaths to maintain stable performance for extended periods in harsh outdoor environments, extending cable lifespan and reducing maintenance and replacement costs. Nano-boron nitride exhibits excellent thermal and chemical stability, high electrical insulation properties, and low polarity. It acts as a good nucleating agent, promoting polyethylene crystallization, resulting in uniform grain distribution, smaller grain size, increased cross-linking, a dense crystalline structure, and reduced grain boundary defects. Inorganic particles, especially nano-sized boron nitride, are prone to agglomeration and have poor compatibility with polyethylene. Modification with alkenylsilane coupling agents is crucial. After hydrolysis, the alkenylsilane coupling agent acquires -OH groups. These -OH groups react with the hydroxyl groups on the surface of the boron nitride nanoparticles, causing them to bond to the surface. This results in uniform dispersion of the boron nitride nanoparticles in polyethylene, reducing agglomeration. Furthermore, the alkenyl groups in the alkenylsilane coupling agent allow it to participate in cross-linking polymerization, improving overall structural strength. Simultaneously, modifying inorganic particles with azobenzene yields superhydrophobic particles, further enhancing their compatibility with polyethylene. The combined modification of inorganic particles with azobenzene and alkenylsilane coupling agents significantly improves the dispersion uniformity, compatibility, and bonding strength of these particles in polyethylene, thereby enhancing the overall mechanical strength, aging resistance, insulation performance, and flame retardant properties of polyethylene cable materials.
[0009] Preferably, the density of the first low-density polyethylene is 0.910-0.925 g / cm³. 3 The density of the second type of low-density polyethylene is 0.898-0.910 g / cm³. 3 The density of high-density polyethylene is 0.94-0.965 g / cm³. 3 .
[0010] Preferably, in the phytic acid-nano TiO2 modified lignin, the mass ratio of nano TiO2, phytic acid and lignin is (1-5):10:(10-25).
[0011] Preferably, in the modified inorganic particle composite material, the mass ratio of magnesium hydroxide and / or aluminum hydroxide, fumed silica, and nano boron nitride is (5-10):(1-5):(5-10), and the mass ratio of the modifier to the inorganic particles is (1-5):1.
[0012] Preferably, the alkenyl silane coupling agent comprises at least one of vinyltrichlorosilane, vinyltrimethoxysilane, vinyltriethoxysilane, vinyl(2-methoxyethoxy)silane, vinyltritert-butoxysilane, alkenyltriacetoxysilane, allyltrimethoxysilane, and allyl glycidyl ether.
[0013] Preferably, the crosslinking agent includes at least one of acrylate crosslinking agents and organic peroxide crosslinking agents. Acrylate compounds can improve the compatibility and crosslinking properties between raw material components, making the surface of the cable material glossy and smooth, while also being less prone to damage. The acrylate groups in its structure also have excellent hydrophobicity.
[0014] Preferably, the organic peroxide crosslinking agent includes at least one of benzamide peroxide, dicumyl peroxide, di-tert-butyl peroxide, and dicumyl peroxide.
[0015] Preferably, the acrylate crosslinking agent includes at least one of methyl acrylate, ethyl acrylate, 2-methyl methacrylate, 2-methyl methacrylate, 1,6-hexanediol diacrylate, trimethylolpropane triacrylate, pentaerythritol tetraacrylate, and tripropylene glycol diacrylate.
[0016] Preferably, the initiator includes at least one of diphenyl ethyl ketone, 2-hydroxy-methylphenylpropane-1-one, 1-hydroxycyclohexylphenyl ketone, 2-hydroxy-2-methylpropanone, 2,4-dihydroxybenzophenone, benzophenone, bisbenzoylphenylphosphine oxide, α-hydroxyalkylphenyl ketone, and α-aminealkylphenyl ketone.
[0017] Preferably, the polyolefin elastomer is SEBS polyolefin elastomer.
[0018] Preferably, the antioxidant includes at least one of hindered phenolic antioxidants and phosphite antioxidants.
[0019] Another objective of this invention is to provide a process for preparing a UV-curable polyethylene cable material with high insulation performance, comprising the following steps:
[0020] 1) Preparation of phytic acid-nano TiO2 modified lignin: phytic acid, nano TiO2 and alkali lignin are dispersed in water, the pH is adjusted to 9-12, and the reaction is carried out at 10-30℃ by ultrasonication or stirring for 10-40 min. The precipitate is collected by filtration, the precipitate is washed until the pH of the filtrate is neutral, and then dried to obtain phytic acid-nano TiO2 modified lignin.
[0021] 2) Preparation of modified inorganic particle composite material: Azobenzene and alkenylsilane coupling agent are dissolved in ethanol aqueous solution to obtain a first mixture. Magnesium hydroxide and / or aluminum hydroxide, as well as fumed silica and nano boron nitride are dispersed in ethanol aqueous solution to obtain a second mixture. The first mixture and the second mixture are then mixed and reacted by ultrasonication or stirring at 40-60℃ for 1-2 hours. After filtration, washing and drying, the modified inorganic particle composite material is obtained.
[0022] 3) Mix the first low-density polyethylene, the second low-density polyethylene, the high-density polyethylene, the phytic acid-nano TiO2 modified lignin, the modified inorganic particle composite material, and the polyolefin elastomer according to the formula amount, and perform a first internal mixing. Add the crosslinking agent, initiator, and antioxidant, and perform a second internal mixing. After the internal mixing is completed, extrude the mixture.
[0023] 4) The obtained extruded material is photocrosslinked in an ultraviolet irradiation device to obtain the ultraviolet-cured polyethylene cable material with high insulation performance.
[0024] Preferably, in step 2), the mass ratio of azobenzene to alkenylsilane coupling agent is 1:(1-2); and the mass ratio of ethanol to water in the ethanol aqueous solution is 10:(1-5).
[0025] Preferably, in step 3), the temperature of the first mixing is 110-140℃ and the time is 10-30 min, and the temperature of the second mixing is 140-170℃ and the time is 10-30 min.
[0026] Preferably, in step 4), the irradiation power for photocrosslinking is 2.0-3.0 mW / cm². 2 The photocrosslinking time is 1-15 min.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] 1. This invention uses a blend of low-density polyethylene and high-density polyethylene, combining the advantages of both to form a cross-linked network with higher cross-linking density. This results in a more stable structure that is less prone to deformation, while also possessing excellent mechanical properties and high toughness, significantly improving the performance of polyethylene cable materials. The introduced phytic acid-nano TiO2 modified lignin exhibits a strong synergistic effect among phytic acid, nano TiO2, and lignin: a large amount of phosphorus (P) is introduced into the lignin through a condensation reaction with phytic acid, significantly improving its flame-retardant properties. Furthermore, the presence of phytic acid allows for better dispersion of lignin particles within the polyethylene. The lignin also significantly reduces the hygroscopicity caused by the addition of phytic acid, and its synergistic effect with nano TiO2 improves the waterproofness of the polyethylene cable material. The introduction of modified inorganic particle composite materials, such as magnesium hydroxide and aluminum hydroxide, provides excellent insulation and flame retardant properties. Fumed silica promotes heterogeneous nucleation, while nano-boron nitride acts as an excellent nucleating agent to promote polyethylene crystallization. The combination of these two materials results in small and uniformly distributed grain growth in low-density polyethylene, enhancing the compactness of the polyethylene material. The use of azobenzene and alkenylsilane coupling agents to modify inorganic particles significantly improves the dispersion uniformity, compatibility, and bonding strength of inorganic particles in polyethylene, thereby enhancing the overall mechanical strength, aging resistance, insulation, and flame retardant properties of polyethylene cable materials.
[0029] 2. The polyethylene cable material obtained by this invention has excellent performance, high safety, and long service life. The temperature gradient generated during the operation of the cable prepared by this invention will not cause changes in the internal structure of the polyethylene cable material, thus effectively slowing down the aging of the polyethylene cable material.
[0030] 3. The preparation process of the present invention is characterized by simple operation, low production cost, and suitability for widespread application. Detailed Implementation
[0031] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0032] All raw materials and equipment used in this invention are commercially available.
[0033] Example 1
[0034] A high-insulation UV-curable polyethylene cable material comprises the following raw materials in parts by weight: density 0.910 g / cm³. 3 The first low-density polyethylene, 50 parts, has a density of 0.898 g / cm³. 3 The second low-density polyethylene, 10 parts, has a density of 0.965 g / cm³.3 The composition includes 20 parts high-density polyethylene, 15 parts phytic acid-nano TiO2 modified lignin, 1 part modified inorganic particle composite material, 1 part SEBS polyolefin elastomer, 0.5 parts benzamide peroxide crosslinking agent, 0.5 parts diphenyl ethyl ketone initiator, and 0.2 parts 1010 antioxidant. The phytic acid-nano TiO2 modified lignin is obtained by the condensation reaction of alkali lignin and phytic acid while simultaneously doping with nano TiO2, with a mass ratio of nano TiO2, phytic acid, and lignin of 1:10:10. In the modified inorganic particle composite material, the inorganic particles include magnesium hydroxide, fumed silica, and nano boron nitride, with a mass ratio of 10:1:5. The modifiers are azobenzene and vinyltrichlorosilane (mass ratio 1:1), with a mass ratio of modifier to inorganic particles of 1:1.
[0035] The preparation process of the UV-curable polyethylene cable material in this embodiment includes the following steps:
[0036] 1) Preparation of phytic acid-nano TiO2 modified lignin: Phytic acid, nano TiO2 and alkali lignin are dispersed in water, the pH is adjusted to 9, and the mixture is stirred at 10℃ for 40 min. The precipitate is collected by filtration, washed with deionized water until the pH of the filtrate is neutral, and dried to obtain phytic acid-nano TiO2 modified lignin.
[0037] 2) Preparation of modified inorganic particle composite material: Azobenzene and vinyltrichlorosilane were dissolved in an aqueous ethanol solution, and magnesium hydroxide, fumed silica and nano boron nitride were dispersed in the aqueous ethanol solution. The mass ratio of ethanol to water in the aqueous ethanol solution was 10:1. The two were then mixed and stirred at 40°C for 2 hours. The solid was collected by filtration, washed three times with deionized water, and dried to obtain the modified inorganic particle composite material.
[0038] 3) Mix the first low-density polyethylene, the second low-density polyethylene, high-density polyethylene, phytic acid-nano TiO2 modified lignin, modified inorganic particle composite material, and polyolefin elastomer according to the weight ratio, and perform a first internal mixer. Add crosslinking agent, initiator, and antioxidant, and perform a second internal mixer. The temperature of the first internal mixer is 110℃ and the time is 30 min. The temperature of the second internal mixer is 140℃ and the time is 30 min. Extrude after the internal mixer is completed.
[0039] 4) The obtained extruded material is subjected to photocrosslinking in an ultraviolet irradiation device with an irradiation power of 2.0 mW / cm². 2 The photocrosslinking time was 12 minutes, resulting in UV-cured polyethylene cable material.
[0040] Example 2
[0041] A high-insulation UV-curable polyethylene cable material comprises the following raw materials in parts by weight: density 0.920 g / cm³.3 The first low-density polyethylene, 80 parts, has a density of 0.910 g / cm³. 3 Two parts of the second low-density polyethylene, with a density of 0.94 g / cm³. 3 The composition includes 10 parts high-density polyethylene, 5 parts phytic acid-nano TiO2 modified lignin, 4 parts modified inorganic particle composite material, 4 parts SEBS polyolefin elastomer, 1.5 parts methyl methacrylate crosslinking agent, 1.5 parts α-amine alkyl phenyl ketone initiator, and 0.8 parts 264 antioxidant. The phytic acid-nano TiO2 modified lignin is obtained by the condensation reaction of alkali lignin and phytic acid while simultaneously doping with nano TiO2, with a mass ratio of nano TiO2, phytic acid, and lignin of 1:2:5. In the modified inorganic particle composite material, the inorganic particles include aluminum hydroxide, fumed silica, and nano boron nitride, with a mass ratio of 5:1:10. The modifiers are azobenzene and allyltrimethoxysilane (mass ratio 1:2), with a mass ratio of modifier to inorganic particles of 5:1.
[0042] The preparation process of the UV-curable polyethylene cable material in this embodiment includes the following steps:
[0043] 1) Preparation of phytic acid-nano TiO2 modified lignin: Phytic acid, nano TiO2 and alkali lignin are dispersed in water, the pH is adjusted to 12, and the mixture is ultrasonically reacted at 30℃ for 10 min. The precipitate is collected by filtration, washed with deionized water until the pH of the filtrate is neutral, and dried to obtain phytic acid-nano TiO2 modified lignin.
[0044] 2) Preparation of modified inorganic particle composite material: Azobenzene and allyltrimethoxysilane were dissolved in an aqueous ethanol solution, and magnesium hydroxide and / or aluminum hydroxide, as well as fumed silica and nano boron nitride were dispersed in the aqueous ethanol solution. The mass ratio of ethanol to water in the aqueous ethanol solution was 2:1. Then the two were mixed and ultrasonically reacted at 60°C for 1 h. After filtration, the mixture was washed three times with deionized water and dried to obtain the modified inorganic particle composite material.
[0045] 3) Mix the first low-density polyethylene, the second low-density polyethylene, high-density polyethylene, phytic acid-nano TiO2 modified lignin, modified inorganic particle composite material, and polyolefin elastomer according to the weight ratio, and perform a first internal mixer. Add crosslinking agent, initiator, and antioxidant, and perform a second internal mixer. The temperature of the first internal mixer is 140℃ and the time is 10 min. The temperature of the second internal mixer is 170℃ and the time is 10 min. Extrude after the internal mixer is completed.
[0046] 4) The obtained extruded material is subjected to photocrosslinking in an ultraviolet irradiation device with an irradiation power of 3.0 mW / cm. 2 The photocrosslinking time was 2 minutes, and ultraviolet-cured polyethylene cable material was obtained.
[0047] Example 3
[0048] A high-insulation UV-curable polyethylene cable material comprises the following raw materials in parts by weight: density 0.915 g / cm³. 3 The first low-density polyethylene, 62 parts, has a density of 0.905 g / cm³. 3 The second low-density polyethylene, consisting of 6 parts, has a density of 0.95 g / cm³. 3 The composition includes 15 parts high-density polyethylene, 10 parts phytic acid-nano TiO2 modified lignin, 2.5 parts modified inorganic particle composite material, 3 parts SEBS polyolefin elastomer, 0.5 parts dicumyl peroxide crosslinking agent, 0.5 parts trimethylolpropane triacrylate crosslinking agent, 1 part 2-hydroxy-2-methylpropanone initiator, and 0.5 parts PEP-8T antioxidant. The phytic acid-nano TiO2 modified lignin is obtained by the condensation reaction of alkali lignin and phytic acid while simultaneously doping with nano-TiO2. The mass ratio of nano-TiO2, phytic acid, and lignin is 3:10:15. In the modified inorganic particle composite material, the inorganic particles include magnesium hydroxide, aluminum hydroxide, fumed silica, and nano-boron nitride, with a mass ratio of 3:3:3:8. The modifiers are azobenzene and alkenyltriacetoxysilane (mass ratio 1:1.5), and the mass ratio of modifier to inorganic particles is 3:1.
[0049] The preparation process of the UV-curable polyethylene cable material in this embodiment includes the following steps:
[0050] 1) Preparation of phytic acid-nano TiO2 modified lignin: Phytic acid, nano TiO2 and alkali lignin are dispersed in water, the pH is adjusted to 10, and the mixture is ultrasonically reacted at 20℃ for 15 min. The precipitate is collected by filtration, washed with deionized water until the pH of the filtrate is neutral, and dried to obtain phytic acid-nano TiO2 modified lignin.
[0051] 2) Preparation of modified inorganic particle composite material: Azobenzene and alkenyltriacetoxysilane were dissolved in an aqueous ethanol solution, and magnesium hydroxide, aluminum hydroxide, fumed silica and nano boron nitride were dispersed in the aqueous ethanol solution. The mass ratio of ethanol to water in the aqueous ethanol solution was 4:1. Then the two were mixed and ultrasonically reacted at 50°C for 1.5 h. After filtration, the mixture was washed three times with deionized water and dried to obtain the modified inorganic particle composite material.
[0052] 3) Mix the first low-density polyethylene, the second low-density polyethylene, high-density polyethylene, phytic acid-nano TiO2 modified lignin, modified inorganic particle composite material, and polyolefin elastomer according to the weight ratio, and perform a first internal mixer. Add crosslinking agent, initiator, and antioxidant, and perform a second internal mixer. The temperature of the first internal mixer is 120℃ and the time is 20 min. The temperature of the second internal mixer is 150℃ and the time is 15 min. Extrude after the internal mixer is completed.
[0053] 4) The obtained extruded material is subjected to photocrosslinking in an ultraviolet irradiation device with an irradiation power of 2.5 mW / cm². 2 The photocrosslinking time was 5 minutes to obtain UV-cured polyethylene cable material.
[0054] Example 4
[0055] A high-insulation UV-curable polyethylene cable material comprises the following raw materials in parts by weight: density 0.920 g / cm³. 3 The first low-density polyethylene, 60 parts, has a density of 0.898 g / cm³. 3 Four parts of the second low-density polyethylene, with a density of 0.95 g / cm³. 3 The composition includes 17 parts high-density polyethylene, 13 parts phytic acid-nano TiO2 modified lignin, 3 parts modified inorganic particle composite material, 2 parts SEBS polyolefin elastomer, 0.8 parts diisopropylbenzene hydrogen peroxide crosslinking agent, 0.7 parts 2-hydroxy-2-methylpropenone initiator, and 0.3 parts 264 antioxidant. The phytic acid-nano TiO2 modified lignin is obtained by the condensation reaction of alkali lignin and phytic acid while simultaneously doping with nano-TiO2, with a mass ratio of nano-TiO2, phytic acid, and lignin of 2:5:10. In the modified inorganic particle composite material, the inorganic particles include magnesium hydroxide, aluminum hydroxide, fumed silica, and nano-boron nitride, with a mass ratio of 1:1:1:2. The modifiers are azobenzene and vinyltriethoxysilane (mass ratio 1:1.2), with a mass ratio of modifier to inorganic particles of 2:1.
[0056] The preparation process of the UV-curable polyethylene cable material in this embodiment includes the following steps:
[0057] 1) Preparation of phytic acid-nano TiO2 modified lignin: Phytic acid, nano TiO2 and alkali lignin are dispersed in water, the pH is adjusted to 11, and the mixture is ultrasonically reacted at 25℃ for 15 min. The precipitate is collected by filtration, washed with deionized water until the pH of the filtrate is neutral, and dried to obtain phytic acid-nano TiO2 modified lignin.
[0058] 2) Preparation of modified inorganic particle composite material: Azobenzene and alkenylsilane coupling agent were dissolved in an ethanol aqueous solution. Magnesium hydroxide, aluminum hydroxide, fumed silica and nano boron nitride were dispersed in the ethanol aqueous solution. The mass ratio of ethanol to water in the ethanol aqueous solution was 5:1. Then the two were mixed and ultrasonically reacted at 45°C for 1 h. After filtration, the mixture was washed three times with deionized water and dried to obtain the modified inorganic particle composite material.
[0059] 3) Mix the first low-density polyethylene, the second low-density polyethylene, high-density polyethylene, phytic acid-nano TiO2 modified lignin, modified inorganic particle composite material, and polyolefin elastomer according to the weight ratio, and perform a first internal mixer. Add crosslinking agent, initiator, and antioxidant, and perform a second internal mixer. The temperature of the first internal mixer is 130℃ and the time is 15 min. The temperature of the second internal mixer is 160℃ and the time is 20 min. Extrude after the internal mixer is completed.
[0060] 4) The obtained extruded material was subjected to photocrosslinking in an ultraviolet irradiation device with an irradiation power of 2.2 mW / cm². 2 The photocrosslinking time was 10 minutes to obtain UV-cured polyethylene cable material.
[0061] Example 5
[0062] A high-insulation UV-curable polyethylene cable material comprises the following raw materials in parts by weight: density 0.915 g / cm³. 3 The first low-density polyethylene, 70 parts, has a density of 0.905 g / cm³. 3 Eight parts of the second low-density polyethylene, with a density of 0.965 g / cm³. 3 The composition includes 12 parts high-density polyethylene, 8 parts phytic acid-nano TiO2 modified lignin, 2 parts modified inorganic particle composite material, 2.5 parts SEBS polyolefin elastomer, 0.7 parts benzamide peroxide crosslinking agent, 0.6 parts trimethylolpropane triacrylate crosslinking agent, 1.2 parts bisbenzoylphenylphosphine oxide initiator, and 0.6 parts PEP-8T antioxidant. The phytic acid-nano TiO2 modified lignin is obtained by the condensation reaction of alkali lignin and phytic acid while simultaneously doping with nano TiO2, with a mass ratio of nano TiO2, phytic acid, and lignin of 2:5:8. In the modified inorganic particle composite material, the inorganic particles include aluminum hydroxide, fumed silica, and nano boron nitride, with a mass ratio of 3:1:3. The modifiers are azobenzene and alkenyltriacetoxysilane, with a mass ratio of modifier to inorganic particles of 1-5:1.
[0063] The preparation process of the UV-curable polyethylene cable material in this embodiment includes the following steps:
[0064] 1) Preparation of phytic acid-nano TiO2 modified lignin: Phytic acid, nano TiO2 and alkali lignin are dispersed in water, the pH is adjusted to 10, and the mixture is ultrasonically reacted at 20℃ for 20 min. The precipitate is collected by filtration, washed with deionized water until the pH of the filtrate is neutral, and dried to obtain phytic acid-nano TiO2 modified lignin.
[0065] 2) Preparation of modified inorganic particle composite material: Azobenzene and alkenyltriacetoxysilane are dissolved in an aqueous ethanol solution, and aluminum hydroxide, fumed silica and nano boron nitride are dispersed in the aqueous ethanol solution. The mass ratio of ethanol to water in the aqueous ethanol solution is 7:1. Then the two are mixed and reacted by ultrasonication or stirring at 40-60℃ for 1-2 hours. After filtration, washing and drying, the modified inorganic particle composite material is obtained.
[0066] 3) Mix the first low-density polyethylene, the second low-density polyethylene, high-density polyethylene, phytic acid-nano TiO2 modified lignin, modified inorganic particle composite material, and polyolefin elastomer according to the weight ratio, and perform a first internal mixer. Add crosslinking agent, initiator, and antioxidant, and perform a second internal mixer. The temperature of the first internal mixer is 130℃ and the time is 15 min. The temperature of the second internal mixer is 150℃ and the time is 20 min. Extrude after the internal mixer is completed.
[0067] 4) The obtained extruded material was subjected to photocrosslinking in an ultraviolet irradiation device with an irradiation power of 2.8 mW / cm². 2 The photocrosslinking time was 3 minutes, resulting in UV-cured polyethylene cable material.
[0068] Comparative Example 1
[0069] The lignin modified with phytic acid-nano TiO2 was not added; otherwise, it was the same as in Example 3.
[0070] Comparative Example 2
[0071] The phytic acid-nano TiO2 modified lignin was replaced with a physical mixture of alkali lignin, phytic acid, and nano TiO2, and the rest was the same as in Example 3.
[0072] Comparative Example 3
[0073] The same as in Example 3 was used for the unmodified inorganic particle composite material.
[0074] Comparative Example 4
[0075] The modified inorganic particle composite material was replaced with a physical mixture of magnesium hydroxide, aluminum hydroxide, fumed silica, and nano boron nitride, with the rest being the same as in Example 3.
[0076] According to JBT10437-2024 "Cross-linkable polyethylene insulation for wires and cables" and GB / T2406.2-2009 "Determination of flammability by oxygen index method for plastics - Part 2: Room temperature test", the cable materials obtained in Examples 1-5 and Comparative Examples 1-4 were tested for performance, and the results are listed in Table 1.
[0077] Table 1
[0078]
[0079] As shown in Table 1, compared with Comparative Examples 1-4, the polyethylene cable materials of Examples 1-5 have good mechanical properties, insulation properties, and flame retardant properties. Their tensile strength is greater than 15 MPa, and the maximum change rate of tensile strength after air oven heat aging (135±2℃, 168h) is between -15% and -10%. Their volume resistivity (20℃) is 1.6 × 10⁻⁶. 14 Ω·m or higher, volume resistivity (90℃) is 1.5×10 10 Ω·m or higher. Comparison of Examples 1-4 in Example 3 revealed that phytic acid-nano TiO2 modified lignin and modified inorganic particle composite materials have a significant impact on the mechanical properties, insulation properties, and flame retardant properties of polyethylene cable materials. Specifically, the modification of phytic acid-nano TiO2 modified lignin, and whether or not phytic acid, nano TiO2, and lignin are modified, have a greater impact on mechanical properties and flame retardant properties. The modified inorganic particle composite material and whether or not the inorganic particles are modified have a greater impact on insulation properties. The polyethylene cable material obtained by this invention possesses excellent mechanical properties, aging resistance, insulation properties, and flame retardant properties, exhibits high safety, and has a long service life.
[0080] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A UV-curable polyethylene cable material with high insulation performance, characterized in that, The raw materials include the following parts by weight: 50-80 parts of first low-density polyethylene, 2-10 parts of second low-density polyethylene, 10-20 parts of high-density polyethylene, 5-15 parts of phytic acid-nano TiO2 modified lignin, 1-4 parts of modified inorganic particle composite material, 1-4 parts of polyolefin elastomer, 0.5-1.5 parts of crosslinking agent, 0.5-1.5 parts of initiator, and 0.2-0.8 parts of antioxidant; wherein the phytic acid-nano TiO2 modified lignin is obtained by polycondensation reaction of alkali lignin and phytic acid while simultaneously doping with nano TiO2; wherein the inorganic particles in the modified inorganic particle composite material include magnesium hydroxide and / or aluminum hydroxide, as well as fumed silica and nano boron nitride, and the modifier is a composition of azobenzene and alkenylsilane coupling agent.
2. The high-insulation-performance UV-cured polyethylene cable material according to claim 1, characterized in that, The density of the first low-density polyethylene is 0.910-0.925 g / cm³. 3 The density of the second type of low-density polyethylene is 0.898-0.910 g / cm³. 3 The density of high-density polyethylene is 0.94-0.965 g / cm³. 3 .
3. The high-insulation-performance UV-curable polyethylene cable material according to claim 1, characterized in that, In the phytic acid-nano TiO2 modified lignin, the mass ratio of nano TiO2, phytic acid and lignin is (1-5):10:(10-25).
4. The high-insulation-performance UV-curable polyethylene cable material according to claim 1, characterized in that, In the modified inorganic particle composite material, the mass ratio of magnesium hydroxide and / or aluminum hydroxide, fumed silica, and nano boron nitride is (5-10):(1-5):(5-10), and the mass ratio of modifier to inorganic particles is (1-5):
1.
5. The high-insulation-performance UV-curable polyethylene cable material according to claim 1, characterized in that, The alkenyl silane coupling agent includes at least one of vinyltrichlorosilane, vinyltrimethoxysilane, vinyltriethoxysilane, vinyltri(2-methoxyethoxy)silane, vinyltritert-butoxysilane, alkenyltriacetoxysilane, allyltrimethoxysilane, and allyl glycidyl ether.
6. The high-insulation-performance UV-curable polyethylene cable material according to claim 1, characterized in that, The crosslinking agent includes at least one of acrylate crosslinking agents and organic peroxide crosslinking agents; The initiator includes at least one of diphenyl ethyl ketone, 2-hydroxy-methylphenylpropane-1-one, 1-hydroxycyclohexylphenyl ketone, 2-hydroxy-2-methylpropanone, 2,4-dihydroxybenzophenone, benzophenone, bisbenzoylphenylphosphine oxide, α-hydroxyalkylbenzophenone, and α-aminealkylbenzophenone.
7. The high-insulation-performance UV-curable polyethylene cable material according to claim 1, characterized in that, The polyolefin elastomer is SEBS polyolefin elastomer; The antioxidants include at least one of hindered phenolic antioxidants and phosphite antioxidants.
8. The preparation process of a high-insulation-performance UV-curable polyethylene cable material according to any one of claims 1-7, characterized in that, Includes the following steps: 1) Preparation of phytic acid-nano TiO2 modified lignin: phytic acid, nano TiO2 and alkali lignin are dispersed in water, the pH is adjusted to 9-12, and the reaction is carried out at 10-30℃ by ultrasonication or stirring for 10-40 min. The precipitate is collected by filtration, the precipitate is washed until the pH of the filtrate is neutral, and then dried to obtain phytic acid-nano TiO2 modified lignin. 2) Preparation of modified inorganic particle composite material: Azobenzene and alkenylsilane coupling agent are dissolved in ethanol aqueous solution to obtain a first mixture. Magnesium hydroxide and / or aluminum hydroxide, as well as fumed silica and nano boron nitride are dispersed in ethanol aqueous solution to obtain a second mixture. The first mixture and the second mixture are then mixed and reacted by ultrasonication or stirring at 40-60℃ for 1-2 hours. After filtration, washing and drying, the modified inorganic particle composite material is obtained. 3) Mix the first low-density polyethylene, the second low-density polyethylene, the high-density polyethylene, the phytic acid-nano TiO2 modified lignin, the modified inorganic particle composite material, and the polyolefin elastomer according to the formula amount, and perform a first internal mixing. Add the crosslinking agent, initiator, and antioxidant, and perform a second internal mixing. After the internal mixing is completed, extrude the mixture. 4) The obtained extruded material is photocrosslinked in an ultraviolet irradiation device to obtain the ultraviolet-cured polyethylene cable material with high insulation performance.
9. The preparation process of a high-insulation-performance ultraviolet-cured polyethylene cable material according to claim 8, characterized in that, In step 2), the mass ratio of azobenzene to alkenylsilane coupling agent is 1:(1-2); the mass ratio of ethanol to water in the ethanol aqueous solution is 10:(1-5).
10. The preparation process of a high-insulation-performance ultraviolet-cured polyethylene cable material according to claim 8, characterized in that, In step 3), the temperature of the first mixing is 110-140℃ and the time is 10-30 min, and the temperature of the second mixing is 140-170℃ and the time is 10-30 min.
Citation Information
Cited By
Anti-aging PE waterproof coiled material and preparation method thereof
CN121182033A